Identification of alleles and genotypes of beta-casein with DNA sequencing analysis in Chinese Holstein cow. Issue 3 (7th September 2016) - Dai, Ronghua; Fang, Yu; Zhao, Wenjing; Liu, Shuyun; Ding, Jinmei; Xu, Ke; Yang, Lingyu; He, Chuan; Ding, Fangmei; Meng, He
Abstract : The study reported in this Regional Research Communication aimed to analyse the genetic polymorphisms of β-casein in Chinese Holstein cows. β-casein has received considerable research interest in the dairy industry and animal breeding in recent years as a source not only of high quality protein, but also of bioactive peptides that may be linked to health effects. Morever, the polymorphic nature of β-casein and its association with milk production traits, composition, and quality also attracted several efforts in evaluating the allelic distribution of β-casein locus as a potential dairy trait marker. However, few data on beta-casein variants are available for the Chinese Holstein cow. In the present paper, one hundred and thirty three Holstein cows were included in the analysis. Results revealed the presence of 5 variants (A1, A2, A3, B and I), preponderance of the genotype A1A2 (0·353) and superiorities of A1/A2 alleles (0·432 and 0·459, respectively) in the population. Sequence analysis of β-casein gene in the cows showed four nucleotide changes in exon 7. Our study can provide reference and guidance for selection for superior milk for industrial applications and crossbreeding and genetic improvement programmes.